The swelling effect of sodium-bentonite as an additive in water-based drilling sludge with different concentration of polyamine inhibition. Issue 6 (March 2021) - Akbar, T; Setiati, R; Akbar, R
Abstract: A highly reactive sludge on drilling progress has become a common problem. The problem will cause swelling clay or high filtration loss. With a risk of swelling appearance and too much filtration loss that may cause, sodium-bentonite is widely used in drilling sludge to give more viscosity and optimal ability to hold and lift the cutting inside the borehole. It contains mostly montmorillonite like particles of sodium that overpower the iolite content inside it. Polyamine as an inhibitor to the clay can infiltrate into the bentonite c-spacing, which is a gap between two layers of bentonite structure. A test has been conducted to measure the effect of polyamine inhibition inside a water-base sludge formulation x that is previously inhibited with sodium-bentonite. These tests were conducted using a number of instruments such as API Filtrate loss, swell meter test, retort oven, and Vann vg meter with API Standard procedure. The result provides a distinctive conclusion about how the rheological elements react toward the polyamine existence with different concentrations (4gr-10, 5gr) inside the sludge. This research also reveals that the sludge durability is different between room temperature and high temperature (300°F).